The Effect of Rotigotine Extended-Release Microspheres Alone or With Celecoxib on the Inflammatory Pain - Li, Keke; Zhang, Yijia; Tian, Enming; Liu, Zikai; Wang, Tian; Fu, Fenghua (Frontiers in Pharmacology, 2020)
Clinical trials of rotigotine extended-release microspheres (RTGT-MS), which provides a sustained release of rotigotine over a 7-day period in vivo, have been conducted in the treatment of Parkinson’s disease (PD). This study was to investigate the analgesic effect of RTGT-MS, and to know whether RTGT-MS have synergistic interaction with non-steroidal anti-inflammatory drug, celecoxb. The inflammatory pain model of rats was prepared by carrageenan-induced paw edema. The thermal and mechanical stimuli were applied and the hindpaw withdrawal latencies (HWLs) response was evaluated. Treatment with RTGT-MS increased the HWLs in a dose-dependent manner. The ED50 of RTGT-MS was 24.68 ± 1.02 mg/kg. Isobolographic analysis shows that the combination of RTGT-MS and celecoxib resulted in a synergistic anti-nociceptive effect. Further results demonstrated that anti-nociceptive effect of RTGT-MS was accompanied with that PKA, cAMP, COX-2, and PGE2 levels were decreased. Chlorpromazine, a dopamine receptor blocker, not only weakened the analgesic effect of RTGT-MS, but also increased the levels of cAMP, PKA, COX-2, and PGE2. These findings provide a rationale for the combination of RTGT-MS and celecoxib in the treatment of PD, which may reduce the dose of celecoxib, thereby lowering the incidence of adverse effects and improving the pain management in PD patients.